A cross-sectional examination of the profile of chiropractors recruited to the Australian Chiropractic Research Network (ACORN): a sustainable resource for future chiropractic research. Issue 9 (29th September 2017) - Adams, Jon; Peng, Wenbo; Steel, Amie; Lauche, Romy; Moore, Craig; Amorin-Woods, Lyndon; Sibbritt, David
Abstract : Objectives: The Australian Chiropractic Research Network (ACORN) practice-based research network (PBRN) cohort was established to provide sustainable infrastructure necessary to address lack of rigorous investigation and to bridge the research–practice gap focused on chiropractic care for future years. This paper presents the profile of chiropractors recruited to the ACORN PBRN, a nationally representative sample of chiropractors working in Australia. Design: Cross-sectional analysis of baseline data from a cohort study of chiropractors in Australia. Setting: All registered chiropractors in Australia were invited to participate in the ACORN study and those who completed a practitioner questionnaire and consent form were included in the PBRN cohort. Participants: A total of 1680 chiropractors (36%) were recruited to the cohort database. The average age of the PBRN participants is 41.9 years and 63% are male. The vast majority of the PBRN participants hold a university degree. Results: General practitioners were identified as the most popular referral source for chiropractic care and low back pain and neck pain were the most common conditions 'often' treated by the PBRN chiropractors. The chiropractors in this PBRN cohort rated high velocity, low amplitude adjustment/manipulation/mobilisation as the most commonly used technique/method and soft tissue therapy as the most frequently employed musculoskeletal intervention in their patient management. Conclusions: The ACORN PBRN cohort constitutes the largest coverage of any single healthcare profession via a national voluntary PBRN providing a sustainable resource for future follow-up. The ACORN cohort provides opportunities for further nested substudies related to chiropractic care, chiropractors, their patients and a vast range of broader healthcare issues with a view to helping build a diverse but coordinated research programme and further research capacity building around Australian chiropractic.